Profiles of rural poverty (Geneva, 1979)
This is a popularised version of a major research publication-Poverty and landlessness in rural Asia-issued by the ILO in 1977, with some additional material on Africa and Latin America to provide a comparative perspective. It shows not only that the "Asian Drama" is still with us, but the new data leave the unmistakable. impression that growth in the past quarter of a century has not succeeded in mitigating the problem of rural poverty in Africa and Latin America. The authors maintain that. nevertheless, policy options for poverty eradication are certainly not beyond the imagination of planners and policy-makers in the Third World, stressing that what is needed above all is an effort of will to face up to the challenge.
Keywords: Poverty .